PENGEMBANGAN PERANGKAT PEMBELAJARAN PERSAMAAN LINGKARAN MENGGUNAKAN PENDEKATAN SAINTIFIK BERBANTUAN GEOGEBRA - Ratna Sari Dewi; Abdur Rahman As'ari; Makbul Muksar (FMIPA UNIVERSITAS NEGERI MALANG, 2020)
This research is a research and development that aims to develop learning tools such as student worksheets (LKS) and lesson plans (RPP) on the circles equation. The approach used is scientific approach with the help of Geogebra.The development is done by following 4D models of development that is only done 3 phases: define, design and development without doing disseminate phase. The quality of development products are Valid, Practical and effective. The validation is done by two validators and after validated the products were tested in the classroom to determine it’s practicality and effectiveness level. The subject of this reasearch were the two validators and 22 students of 11th grade senior high school.Keywords: circles equation, scientific approach, geogebra, learning tools